Optical Trapping and Manipulation From Fundamentals to Applications - Jones, Philip; Burnham, Daniel R. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
We are pleased to present "Optical Trapping and Manipulation: From Fundamentals to Applications", a Special Issue of Micromachines dedicated to the latest research in optical trapping. In recognition of the broad impact of optical manipulation techniques across disciplines, this Special Issue collected contributions related to all aspects of optical trapping and manipulation. Both theoretical and experimental studies were welcome, and applications of optical manipulation methods in fields including (but not limited to) single molecule biophysics, cell biology, nanotechnology, atmospheric chemistry, and fundamental optics were particularly welcome in order to showcase the breadth of the current research. The Special Issue accepted diverse forms of contributions, including research papers, short communications, methods, and review articles representing the state-of-the-art in optical trapping.